Queer and Trans People of Colour in the UK Possibilities for Intersectional Richness - Davis, Stephanie (Transforming LGBTQ Lives, 2023)
This book explores the meanings of Queer and Trans People of Colour (QTPOC) activist groups in the UK, considering the tensions around inclusion and belonging across lesbian, gay, bisexual, trans, and queer (LGBTQ) and of colour communities and wider British society. Davis draws de-/anti-/post-colonial, Black feminist, and queer theory into critical psychology to publish the first book of its kind in the UK, developing an intersectional understanding of QTPOC subjectivities and identities. The book examines questions of belonging; racial melancholia; decolonising gender and sexualities; and the joys, erotics, and the difficulties of building and finding QTPOC community that can hold and celebrate our intersectional richness. Offering a radical and critical intervention into psychology, this volume will be of key interest to scholars in Gender Studies and Queer Studies, Psychology and Race, together with activists, community organisers, counsellors, and the third sector.